Impact of COVID-19 on Orthopaedic and Trauma Service: An Epidemiological Study. (15th July 2020) - Wong, Janus Siu Him; Cheung, Kenneth Man Chee
Abstract : Background: Coronavirus disease 2019 (COVID-19) has caused substantial disruptions to orthopaedic and trauma services. The purpose of the present study was to quantify its impact on surgical volume, hospitalizations, clinic appointments, and accident and emergency attendances to guide staffing and resource deployment for the sustenance of emergency services. Methods: Data were retrieved from all 43 Hong Kong public hospitals and 122 outpatient clinics from a population of 7.5 million residents. The "COVID-19 cohort" of patients who received treatment from January 25 to March 27, 2020, was compared with the "control cohort" of patients who received treatment during the same time of year over the past 4 years. Primary outcomes consisted of changes in patient diagnoses, number of operations performed, and hospitalizations during the COVID-19 pandemic. Secondary outcomes included differences in patient age and comorbidity, the nature of operations performed, types of anesthesia for orthopaedic procedures, difference in anesthetic times, wait times, and personal protective equipment (PPE) reserves. Results: A total of 928, 278 patient-episodes (32, 613 operations, 97, 648 hospital admissions, 302, 717 accident and emergency attendances, and 495, 300 outpatient clinic attendances) were analyzed. Orthopaedic operations were reduced by 44.2%, from a mean (and standard deviation) of 795 ± 115.1 to 443.6 ± 25.8 per week (p < 0.001), with the ratio of emergency to elective operations increasing from 1.27:1 to 3.78:1. Operations for the treatment of upper and lower-limb fractures decreased by 23% (from 98.5 ± 14 to 75.9 ± 15.2 per week; p < 0.001) and 20% (from 210.6 ± 29.5 to 168.4 ± 16.9 per week; p < 0.001), respectively, whereas elective joint replacement and ligamentous reconstruction procedures decreased by 74% to 84% (p < 0.001). Operations for orthopaedic infections such as necrotizing fasciitis and septic arthritis remained similar (p > 0.05). The number of hospitalizations decreased by 41.2% (from 2, 365 ± 243 to 1, 391 ± 53 per week; p < 0.001), whereas clinical outpatient visits decreased by 29.4% (from 11, 693 ± 2, 240 to 8, 261 ± 1, 104 per week; p < 0.001). Patients did not endure longer wait times for emergency operations and accident and emergency consultations (p > 0.05). PPE consumption did not exceed procurement, with net increases in PPE reserves. Conclusions: Demand for orthopaedic care remains, despite weekly reductions of 351 orthopaedic operations, 974 hospital admissions, and 3, 432 clinic attendances. Orthopaedic surgeons and health-care professionals should factor this into consideration during staffing and resource deployment. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.